Malaysian Neurointerventional Society (MYNIS) Antiplatelets Guidelines in Endovascular Treatment - Kamis, Mohd Fandi Al Khafiz; Isa Azzaki Zainal (Journal Of Cardiovascular, Neurovascular & Stroke, 2024)
-